Deconstructing Multiculturalism: How Government Policy Is Reflected In Current Education And Practice - Nilsen, Kirsti E. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Canadian multi-cultural policy background, history and recent changes in emphasis is reviewed, and implications for LIS practice and education are considered. Definitional problems are identified. Information gained from interviews with practitioners in two cities provide a current snapshot and will guide future research on mulitculturalism practice in Canadian public libraries. In addition, preliminary findings are presented...